DEVELOPING AUTHENTIC MATERIAL OF LISTENING ON HIGHER EDUCATION BASED ON CONSTRUCTIVE LEARNING OF JEAN PIAGET AND VYGOTSKY THEORY - Erna Nurkholida (OKARA: Jurnal Bahasa dan Sastra, 2018)
Developing authentic material for students is a vital point. Teachers need to design material which meets the students’ potential needs. The purpose of this study is to design and to develop authentic listening materials for second-semester students of IAIN Kediri based on constructive theory of Jean Piaget and Vygotsky. The method used is the Research and Development. The result is a product of listening materials under those programs. This product was tried to the 35 students as samples, as well as the revision of the product. The results obtained the validity of teaching materials that cover the content, construct, and technical validity worth 3.80 at the stage of the testing expert with valid criteria. Data regarding the practicality has a value of 4.33 with the criteria “very practical”. While the results of research on the effectiveness of teaching materials shown positive response obtained from teachers and students as users of the product. After revision, the value of the effectiveness of teaching materials in the test phase to Master 4.25 and 4.39 with the criteria to students “very effective”. The average effectiveness of teaching materials was 4.32 with “very effective” criteria. Teachers and students concluded that the program is effective.